The change in the level of responsibility in the rehabilitation process of persons suffering from drug addiction - Tatiana A. Serezhko; Natalia M. Volobueva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The study is devoted to the study of changes in the level of responsibility in the process of rehabilitation of people suffering from drug addiction. As research methods used: bibliographic review of foreign and domestic psychological literature, testing, quantitative and qualitative analysis of empirical data. The study was conducted in three stages, which were based on the allocation of the system of organizational and methodological tools and research principles.At the first stage, it was found that drug addicts who are beginning rehabilitation have low rates of responsibility. This is especially true in such areas of life as: the scope of failures in activities, the sphere of family relations, the sphere of interpersonal relations, health, which is primarily due to a lack of understanding of the meaning of responsibility and its role in human life and their own. Drug addicts can not cope with the negative emotions that arise at a time when the activity or situation is quite complex.At the second stage, the author monitored the course of the rehabilitation process and participated in its psychological support. Individual consultations, psychological trainings and group psychotherapy were included in a single process of rehabilitation of drug addicts, which we observed and analyzed for six months.At the third stage, respondents were examined after rehabilitation and found that they have acquired the ability to self-reliance and responsible performance of tasks and assignments.Comparison of the results of the study of responsibility before and after rehabilitation shows that in the process of rehabilitation there are changes in the responsibility of drug addicts. It is revealed that after rehabilitation the respondents significantly changed (increased) indicators of responsibility, which has a positive impact on the formation of attitudes to health in the context of dependent behavior.